Hostile/Helpless maternal representations in pregnancy and later child removal: A pilot study. Issue 1 (20th August 2020) - Terry, Madeleine; Finger, Brent; Lyons‐Ruth, Karlen; Sadler, Lois S.; Slade, Arietta
ABSTRACT: This article presents the results of a small pilot study examining links between Hostile/Helpless (HH) representations of caregiving in pregnancy and later child removal by child protective services. The sample was drawn from a replication study of the Minding the Baby ® attachment‐based home‐visiting intervention conducted in the United Kingdom, serving young first‐time mothers in under resourced communities. The HH classification system (Lyons‐Ruth et al.) was adapted for use with the Pregnancy Interview (PI) (Slade); 26 PIs were assessed (coders blinded) in a sample that included 13 mothers whose infants were removed from custody due to anticipated or documented maltreatment within 2 years of childbirth, and 13 mothers who did not have their infants removed. Mothers whose infants were removed from their custody had significantly higher HH scores than mothers of infants who were not removed from their care ( F (1, 24) = 14.500, p < .001), and the relation between overall HH classification and infant removal status was also significant ( χ 2 (1, N = 26) = 12.462, p < .001). Results suggest that prenatal maternal caregiving representations may predict postnatal relationship disruptions, and indicate the need for larger studies further testing this prenatal approach to maltreatment risk assessment in at‐risk populations. RESUMEN: Este artículo presenta los resultados de un pequeño estudio piloto que examina las conexiones entre las representaciones Hostiles/Indefensas de la prestación de cuidado durante el embarazo y más tarde cuando los servicios de protección a la niñez han separado al niño. El grupo muestra fue seleccionado de un estudio de replicación de la intervención Cuidando al Bebé (Minding the Baby® ‐MTB) de visita a casa con base en la afectividad, llevada a cabo en el Reino Unido para servirles a madres jóvenes en comunidades de pocos recursos. El sistema de clasificación Hostil/Indefensa (HH) (Lyons‐Ruth et al., 1995–2005) se adaptó para el uso con la Entrevista del Embarazo (PI) (Slade, 2011); se evaluaron 26 entrevistas PI (los codificadores lo hicieron de manera ciega), de un grupo muestra que incluía 13 madres cuyos infantes fueron separados de su custodia debido al anticipado o documentado maltrato dentro de los 2 años anteriores al parto, y 13 madre cuyos infantes no habían sido separados. Las madres cuyos infantes habían sido separado de su custodia presentaron significativamente más altos puntajes HH que las madres de infantes no separados del cuidado materno (F(1, 24) = 14.500, p < .001), y la relación entre la clasificación general HH y la condición de separación del infante fue también significativa (c2(1, N = 26) = 12.462, p < .001). Los resultados sugieren que las representaciones prenatales del cuidado materno pudieran predecir las interrupciones de la relación postnatal, y apuntan a la necesidad de estudios más comprensivos que continúen examinando este acercamiento prenatal a la evaluación del riesgo de maltrato en grupos bajo riesgo. RÉSUMÉ: Cet article présente les résultats d'une petite étude pilote examinant les liens entre les représentations Hostile/Impuissant du mode de soin durant la grossesse et plus tard durant le retrait de l'enfant par les services de protection de l'enfance. Cet échantillon a été retiré d'une étude de réplication de l'intervention sur l'attachement et faite à domicile Minding the Baby (MTB), faite au Royaume Unis, servant de jeunes mères n'ayant pas eu d'enfant auparavant dans des communautés n'ayant pas beaucoup de ressources. Le système de classification HI suivant les initiales en français Hostile/Impuissant (Lyons‐Ruth et al., 1995–2005) a été adapté pour une utilisation durant l'Entretien de Grossesse (abrégé selon le français EG ici, Slade, 2011). 26 EG ont été évalués (codage à l'aveugle) dans un échantillon qui a inclus 13 mères dont les bébés avaient été retirés de leur garde pour maltraitance documentée ou anticipée dans les deux ans après la naissance, et 13 mères dont les bébés n'avaient pas été retirés. Les mères dont les bébés avaient été retirés de leur garde avaient des scores HI bien plus élevés que les mères de bébés n'avaient pas été retirés de leur garde (F(1, 24) = 14, 500, p <, 001), et la relation entre la classification générale HI et le statut de retrait du bébé était aussi importante (c2(1, N = 26) = 12, 462, p <, 001). Les résultats suggèrent que les représentations de mode de soin maternel prénatal peuvent prédire des perturbations de la relation postnatale, et indiquent le besoin d'études plus grandes testant plus profondément cette approche prétanale de l'évaluation de risque de maltraitance chez des populations à risque. ZUSAMMENFASSUNG: Feindliche / hilflose mütterliche Repräsentationen in der Schwangerschaft und bei der späteren Inobhutnahme der Kinder: Eine Pilotstudie Dieser Artikel präsentiert die Ergebnisse einer kleinen Pilotstudie, in der Zusammenhänge zwischen feindlichen / hilflosen Repräsentationen von der Pflege des Kindes während der Schwangerschaft und der späteren Inobhutnahme durch den Jugendschutz untersucht wurden. Die Stichprobe stammt aus einer Replikationsstudie der im Vereinigten Königreich durchgeführten, bindungsbasierten Hausbesuchsintervention Minding the Baby® (MTB) für jungen Erstmütter aus sozial benachteiligten Gemeinden. Das Klassifizierungssystem Feindlich/Hilflos (Hostile/Helpless; HH; Lyons‐Ruth et al., 1995–2005) wurde für die Verwendung mit dem Schwangerschaftsinterview (Pregnancy Interview; PI; Slade, 2011) angepasst. In einer Stichprobe bestehend aus 13 Müttern, deren Säuglinge aufgrund einer antizipierten oder dokumentierten Misshandlung innerhalb von 2 Jahren nach der Geburt in Obhut genommen wurden, und 13 Müttern, die ihre Säuglinge behalten haben, wurden insgesamt 26 PI's ausgewertet. Mütter, die das Sorgerecht für ihre Säuglinge verloren, hatten signifikant höhere HH‐Werte als Mütter von Säuglingen, die das Sorgerecht behielten (F (1, 24) = 14.500, p <0, 001). Außerdem war der Zusammenhang zwischen der gesamten HH‐Klassifizierung und dem Inobhutnahme‐Status signifikant (2 (1, N = 26) = 12, 462, p <0, 001). Die Ergebnisse deuten darauf hin, dass pränatale mütterliche Repräsentationen von der Pflege des Kindes Störungen der postnatalen Beziehung vorhersagen können und dass größere Studien erforderlich sind, um diesen pränatalen Ansatz zur Risikobewertung von Misshandlungen in Risikopopulationen weiter zu testen. 抄録: 妊娠期における敵対/無力的な母親表象とその後の子どもの引き離し:予備研究 本論文では、妊娠期の敵対/無力的な養育者表象と、児童保護サービスによるそ の後の子どもの引き離しの間の関連について研究した小さな予備研究の結果を示 す。サンプルは、社会資源が十分にない地域の若い初めて母親になる人を対象に、 英国において実施されたアタッチメントを基盤とした家庭訪問介入である Minding the Baby® (MTB)の再現研究から抽出された。敵対/無力(HH) 分類シス テム(Lyons‐Ruth et al., 1995–2005)は、妊娠期インタビュー(PI) (Slade, 2011)と共に使用するのに微修正された。26 のPIが評価された(先入観なしの評 価者)が、その標本は、子どもの誕生後2年以内に虐待を予期あるいは記録された ことによってその保護から引き離された乳幼児の13人の母親と、引き離されてい ない乳幼児の13人の母親であった。親の保護から引き離された乳幼児の母親らは、 母親のケアから引き離されていない乳幼児の母親よりも、HHスコアが優位に高か った (F(1, 24) = 14.500, p < .001)。そして、全体的なHH分類と乳幼児の引き 離しの状況の間の関係もまた有意であった(2(1, N = 26) = 12.462, p < .001)。 結果は、出生前の母親の養育者表象は、出産後の関係の混乱を予測するかも知れ ないことを示唆し、リスクのある集団に虐待リスク評価をするこの出生前アプロ ーチをさらに試験し、より広く研究する必要性を指摘している。 摘要: 本文介绍了一项小规模试点研究的结果, 该研究考察了怀孕期间敌对/无助的照顾行为与儿童保护服务机构随后将儿童带走之间的联系。该样本来自于在英国进行的基于依恋的家访干预"照顾婴儿" (MTB) 的复制研究, 该研究服务于资源不足的社区中的首次怀孕的年轻母亲。敌对/无助 (HH) 分类系统 (Lyons‐Ruth et al., 1995–2005) 适用于妊娠期访谈 (PI) (Slade, 2011);在一个样本中评估了26个PI (编码员不知情), 其中包括13个在分娩后2年内由于预期或有记录的虐待而被剥夺监护权的母亲, 以及13个没有被带走婴儿的母亲。被剥夺婴儿监护权的母亲的HH得分明显高于未被剥夺婴儿监护权的母亲 (F(1, 24) = 14.500, p < .001), 整体HH分类与婴儿移除状态之间的关系也很显著 (2(1, N = 26) = 12.462, p < .001)。结果表明, 产前母亲照顾行为表现可能预测产后关系中断, 并表明需要进行更大规模的研究, 进一步在高危人群中测试这种产前虐待风险评估方法。 ملخص: تقدم هذه المقالة نتائج دراسة تجريبية صغيرة تدرس الروابط بين التصرفات العدائية / العاجزة في تقديم الرعاية الأمومية في الحمل وإبعاد الأطفال في وقت لاحق من خلال خدمات حماية الطفل. وقد استُمدت العينة من دراسة مكررة لدراسة (Minding the Baby, MTB) المنزلية القائمة على التعلق والتي أجريت في المملكة المتحدة لخدمة الأمهات الشابات لأول مرة في المجتمعات المحلية التي لديها موارد قليلة. تم إستخدام نظام تصنيف التصرفات العدائية /العاجزة (HH) (ليونز روث وآخرون، 1995–2005) في مقابلة الحمل (PI) (سليد، 2011)؛ وتم تقييم 26 مقابلة في عينة شملت 13 من الأمهات التي تم أخذ الطفل من حضانتهم بسبب سوء المعاملة المتوقع أو الموثق في غضون عامين من الولادة، و13 من الأمهات اللاتي لم يؤخذ منهن أطفالهن. سجلت الأمهات في المجموعة الأولى درجات ((HH أعلى بكثير الأمهات في المجموعة الثانية وكانت العلاقة بين التصنيف الكلي لـ HH وحالة أخذ الرضع كبيرة أيضاً. وتشير النتائج إلى أن تمثيلات رعاية الأمومة قبل الولادة قد تتنبأ بانقطاعات العلاقات بعد الولادة وتشير إلى الحاجة إلى مزيد من الدراسات لإجراء مزيد من الاختبارات على هذا النهج قبل الولادة لتقييم مخاطر سوء المعاملة لدى الفئات السكانية عالية المخاطرة.